PENGARUH IDENPENDENSI, PENGALAMAN, DAN WORK-LIFE BALANCE AUDITOR TERHADAP KUALITAS LABA (Media Riset Akuntansi, 2022)
This research is intended to obtain the evidence of the influence of auditors’ independency, knowledge, work experience, and work-life balance on audit quality. This research belongs to quantitative research. This research utilized primary data which was collected by using questionnaires and measured by the Likert scale. The amount of samples in this research were 49 respondents that selected by using purposive sampling method. These respondents were auditors who conducted the examination function on Badan Pemeriksa Keuangan Republik Indonesia. The data analysis techniques in this research used multiple linear regression which processed by using SPSS 23 for Windows. It could be inferred that (1) auditors independency affected audit quality, (2) auditors knowledge affected audit quality, (3) auditors work experience affected audit quality, (4) auditors work-life balance did not affect audit quality.